Regulation of Cardiac Remodeling by Cardiac Na+/K+-ATPase Isoforms - Liu, Lijun; Wu, Jian; Kennedy, David J. (Frontiers in Physiology, 2016)
Cardiac remodeling occurs after cardiac pressure/volume overload or myocardial injury during the development of heart failure and is a determinant of heart failure. Preventing or reversing remodeling is a goal of heart failure therapy. Human cardiomyocyte Na+/K+-ATPase has multiple α isoforms (1-3). The expression of the α subunit of the Na+/K+-ATPase is often altered in hypertrophic and failing hearts. The mechanisms are unclear. There are limited data from human cardiomyocytes. Abundant evidences from rodents show that Na+/K+-ATPase regulates cardiac contractility, cell signaling, hypertrophy and fibrosis. The α1 isoform of the Na+/K+-ATPase is the ubiquitous isoform and possesses both pumping and signaling functions. The α2 isoform of the Na+/K+-ATPase regulates intracellular Ca2+ signaling, contractility and pathological hypertrophy. The α3 isoform of the Na+/K+-ATPase may also be a target for cardiac hypertrophy. Restoration of cardiac Na+/K+-ATPase expression may be an effective approach for prevention of cardiac remodeling. In this article, we will overview: (1) the distribution and function of isoform specific Na+/K+-ATPase in the cardiomyocytes. (2) the role of cardiac Na+/K+-ATPase in the regulation of cell signaling, contractility, cardiac hypertrophy and fibrosis in vitro and in vivo. Selective targeting of cardiac Na+/K+-ATPase isoform may offer a new target for the prevention of cardiac remodeling.